A CRITICAL EXAMINATION OF GENDER INEQUALITY IN ALICE WALKER’S MAJOR FICTION - S. P., Sangeeth (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since literature came into existence, women have been there. However, it is quite unfortunate that at various points in time, women wrote about themselves as fragile, inferior, incapable of surviving on their own, unemployed, or generous. Women are beautiful and obedient. They cannot think on their own, according to the guy. Much of the essence of females remained insignificant to love, and they were never permitted to share their experiences, according to the view of Alice Walker. They are also oblivious to how to account for the violation of their self-worth. They are suppressed in many ways; the black community women are misconstrued even in their community. Social, physical, and sexual oppression against black women has always been there, and because of that, they try to break free from that domination. Most black women are treated as slaves who want to redefine their womanhood and end the bondage forced upon them during slavery. This is a paper trying to subjugate and hide black women under suppression, slavery, gender discrimination, and how they differ. It studies black women’s subjugation, self-realization, awakening, and self-emancipation. An Afro-American writer, Alice Walker, meets for the liberation of black women. He evinces solidarity with black women about their relationship with women who have historically built bridges for them with their indomitable spirit and versatile independence. The paper’s argument, in short, shall be to defeat the sufferings of black women. The paper’s argument, in short, shall be to defeat the sufferings of black women.